ANALYSIS OF FINANCING RESTRUCTURING POLICY TO IMPROVE COLLECTIBILITY AND FINANCIAL PERFORMANCE - David Kurniawan; Desi Wahyuni (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to analyze the role of the financing restructuring policy in improving financing collectibility and maintaining financial performance at BMT Mitra Sejahtera Mandiri. This research employs a mixed-methods approach with a descriptive design. Quantitative data were analyzed using financing collectibility indicators and the Non-Performing Financing (NPF) ratio obtained from the institution's internal reports, while qualitative data were obtained through in-depth interviews with the institution's management to explore the mechanisms and considerations underlying the restructuring policy. The results of the study indicate that financing restructuring carried out through rescheduling, reconditioning, and restructuring functions as both a corrective and preventive risk management strategy. This policy helps prevent financing classified under special mention from developing into non-performing financing, as well as supports the stability of the financing portfolio. Furthermore, the restructuring policy contributes to maintaining the institution's cash flow and preserving its financial intermediation function. From an Islamic economic perspective, this policy reflects a balance between prudent financial management and social values such as justice and mutual assistance. Overall, financing restructuring serves as an adaptive risk management instrument in supporting the financial sustainability of Islamic microfinance institutions.